(De)constructing Dasein in Cyberspace: On “Essence” of a Digital Being from Lacanian Understanding - Roy, Swapna (Tattva journal of philosophy, 2024)
Human beings are ontological designers. We build the tools, and then the tools reshape our identities. The ontological status in an electronically mediated world always implies a referential whole, a “totality” that endows “language”, “events,” and “actions” with meaning and significance. The ontological discourse is all about the chain of signifiers; surprisingly, the events of appropriation by which the being is (un)folded depend on a synchronic axis. The twist is that the axis can only be visible on a diachronic background. Questions of the existence of a digital being are always associated with the notions of time and space. Being-in is different than being in as it is located in the “now.” The spatiality of “now” in cyberspace is essential as this “now” talks about the forms of time—past, present and future of Dasein via the unconscious. Each post we share, and each comment we put on cyberspace opens the possibilities for new ways of thinking—a thinking pattern involves the other avatars through the interplay of who they are and what they experience in “the desert of the real” (Zizek, 2001, p. 13).  Thus, the function of the “in-between” becomes différance, and in this act of deferral emerges the prospect of “poíēsis.” Bernard Stiegler, in his book Techniques and Time: The Fault of Epimetheus (1998, p.140), describes that the epiphylogenesis of man “[b]estows its identity upon the human individual: the accents of his speech, the style of his approach, the force of his gesture, the unity of his world.” Identity is like a (un)concealed truth, a whole of potentialities yet to be discovered but never arrive at the ending.  Language is a special equipment to understand the notions of identity, especially in the Heideggerian world, where “essence” precedes “existence”. That is why we refer to beings in their connection to other beings. To know why and how they connect to other beings and even to the digital “spectre” (in Derridean understanding), we must revisit the Lacanian understanding of lack and Freud’s tripartite structure of the human psyche. The subject splits in the course of its striving to fulfil the lack forged by the desire of others. Therefore, the signifying chain is an automata—a lifeless network of signified jouissance in the virtual world.  Lacan’s Seminar XI is primarily taken up for its potential to radically suspend Heideggerian questions of the primary meaning of Being. Therefore, this paper shall explore the genealogy of the “essence” of a digital being taking up multiple roles in a true post-human world by highlighting the newly emerged socio-cultural avenues cohabited with artificial intelligence and human beings—a world where the matrix disguises itself in its simulation. Keywords: Dasein, Unconscious, Simulacra, Cyberspace, Lacan